2013
DOI: 10.1155/2013/815218
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Paid Work and Mental Health Problems among Poor Urban 9‐to‐13‐Year‐Old Children in Brazil

Abstract: Objective. To verify if emotional/behavioral problems are associated with lifetime paid work in poor urban children, when taking into account other potential correlates. Methods. Cross-sectional study focused on 9-to-13-year-old children (n = 212). In a probabilistic sample of clusters of eligible households (women 15–49 years and son/daughter <18 years), one mother-child pair was randomly selected per household (n = 813; response rate = 82.4%). CBCL/6-18 identified child emotional/behavioral problems. Potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…These findings on the effects of child labour are not surprising and reflect the large body of literature on the harmful effects of child labour, including studies in Brazil [19], Ethiopia [20] and India [21], where there are reported associations between hazardous/child labour and poor psychosocial well-being. The current study adds to the evidence base by demonstrating that children working under hazardous work conditions with/without child labour have greater psychosocial functioning difficulty.…”
Section: Discussionsupporting
confidence: 61%
“…These findings on the effects of child labour are not surprising and reflect the large body of literature on the harmful effects of child labour, including studies in Brazil [19], Ethiopia [20] and India [21], where there are reported associations between hazardous/child labour and poor psychosocial well-being. The current study adds to the evidence base by demonstrating that children working under hazardous work conditions with/without child labour have greater psychosocial functioning difficulty.…”
Section: Discussionsupporting
confidence: 61%
“…Among the few studies that have been conducted, emotional disorders are found to be more common among child laborers than non-laborers [17][18][19][20]. Time spent on hard and repetitive work, over which children have little control, is identified as a cause of demoralization [21] and exhaustion [22]. Work that keeps children away from their homes or peers is a cause of isolation [14,21,23], and work that forces children to leave school causes the loss of social and educational opportunities [14,21,22].…”
Section: Study Of Working Children's Wellbeingmentioning
confidence: 99%
“…Time spent on hard and repetitive work, over which children have little control, is identified as a cause of demoralization [21] and exhaustion [22]. Work that keeps children away from their homes or peers is a cause of isolation [14,21,23], and work that forces children to leave school causes the loss of social and educational opportunities [14,21,22]. Work can also be a place where the child is subjected to abuse and violence [24,25] and increased risks of accidents [26][27][28].…”
Section: Study Of Working Children's Wellbeingmentioning
confidence: 99%
“…Few studies investigated the role of gender in perpetuating social inequality. This research sheds light on traditional patriarchal norms (sometimes based on religious belief), exposing women to greater social and financial vulnerability ( 46 , 47 ). When gender inequalities were conjoined with socioeconomic stratification (class), compelling evidence of social inequality emerged.…”
Section: Resultsmentioning
confidence: 99%